1998
DOI: 10.1097/00005392-199812010-00084
|View full text |Cite
|
Sign up to set email alerts
|

Hypospadias Is Related to Birth Weight in Discordant Monozygotic Twins

Abstract: Environmental factors associated with low birth weight are involved in the etiology of hypospadias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 9 publications
2
37
0
Order By: Relevance
“…The results of this study, showing both low weight and length at birth in children with MPH of undefined aetiology, confirm the data of previous studies [4,5,6,12,14] demonstrating an association between intrauterine growth retardation and genital ambiguity in male patients. Our results also show that birth length was more severely decreased than birth weight, indicating that early intrauterine growth retardation may be associated with abnormal testicular differentiation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study, showing both low weight and length at birth in children with MPH of undefined aetiology, confirm the data of previous studies [4,5,6,12,14] demonstrating an association between intrauterine growth retardation and genital ambiguity in male patients. Our results also show that birth length was more severely decreased than birth weight, indicating that early intrauterine growth retardation may be associated with abnormal testicular differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, several articles have been published indicating a possible relationship between idiopathic MPH or isolated hypospadias and prenatal growth retardation. In 1998, Fredell et al [6], studying 18 pairs of monozygotic twins, reported a significant increase in the frequency of hypospadias in the twin with a lower birth weight. In 1999, Francois et al [5], studying 29 children with MPH, observed a higher frequency of low birth weight and complications in early pregnancy among cases of idiopathic MPH.…”
Section: Introductionmentioning
confidence: 99%
“…A study of 18 twin pairs in which one twin had hypospadias and one did not, found that in 16 pairs, the healthy twin brother weighed on average 500 g more at birth than the twin with hypospadias [28]. As monozygotic twins share the same intrauterine environment and genotype, this study supports the hypothesis that fetal growth and the risk of hypospadias are strongly associated.…”
Section: Hypospadiassupporting
confidence: 77%
“…The strongest indication of an association between intrauterine growth and hypospadias comes from monozygotic twins [28, 29]. A study of 18 twin pairs in which one twin had hypospadias and one did not, found that in 16 pairs, the healthy twin brother weighed on average 500 g more at birth than the twin with hypospadias [28].…”
Section: Hypospadiasmentioning
confidence: 99%
“…One possible explanation is that placental insufficiency in providing the fetus with nutrients and gonadotropins may lead to both growth retardation and hypospadias [13,14,17,34]. Placental insufficiency may also explain the increased occurrence of hypospadias in twins [13,14,34]. However, familial clustering suggests a genetic component in the etiology of hypospadias [12].…”
mentioning
confidence: 99%